2005
DOI: 10.1128/jb.187.22.7876-7880.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Essential Two-Component Signal Transduction System, YhcSR, inStaphylococcus aureus

Abstract: Two-component signal transduction systems play an important role in the ability of bacteria to adapt to various environments by sensing changes in their habitat and by altering gene expression. In this study, we report a novel two-component system, YhcSR, in Staphylococcus aureus which is required for bacterial growth in vitro. We found that the down-regulation of yhcSR expression by induced yhcS antisense RNA can inhibit and terminate bacterial growth. Moreover, without complementary yhcS or yhcR, no viable y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 42 publications
4
51
0
1
Order By: Relevance
“…Furthermore, microarray analysis in this study reveals that NsaRS is responsible for regulation of another TCS, yhcSR. Previous studies with cells depleted for yhcSR reveal elevated sensitivity to this antibiotic (Sun et al, 2005), suggesting interplay between these two systems when sensing phosphomycin-mediated damage. Further to this, using a plate-based screening assay, we demonstrate that ampicillin and penicillin G, both of which are involved in extracellular peptidoglycan cross-linking, results in increased nsaRS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, microarray analysis in this study reveals that NsaRS is responsible for regulation of another TCS, yhcSR. Previous studies with cells depleted for yhcSR reveal elevated sensitivity to this antibiotic (Sun et al, 2005), suggesting interplay between these two systems when sensing phosphomycin-mediated damage. Further to this, using a plate-based screening assay, we demonstrate that ampicillin and penicillin G, both of which are involved in extracellular peptidoglycan cross-linking, results in increased nsaRS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis of the YhcR amino acid sequence revealed that YhcR has more than 30% identity with the NarL protein, suggesting that the YhcSR system may belong to the NarL family and be associated with regulation of the nitrate respiratory pathway in S. aureus (data not shown). A TetR-regulated antisense RNA technology has been successfully used to investigate gene function in S. aureus (10,29). Our previous studies have demonstrated that induced yhcS antisense RNA can effectively downregulate endogenous yhcR expression (29).…”
Section: Resultsmentioning
confidence: 99%
“…A TetR-regulated antisense RNA technology has been successfully used to investigate gene function in S. aureus (10,29). Our previous studies have demonstrated that induced yhcS antisense RNA can effectively downregulate endogenous yhcR expression (29). In order to test whether YhcSR is involved in regulation of the nitrate respiratory pathway, we utilized the same TetR-regulated yhcS antisense RNA expression system and examined the impact of downregulating yhcSR expression on growth in the presence or absence of nitrate under anaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations